A real-time quantitative assay for hepatitis B DNA virus (HBV) developed to detect all HBV genotypes Ensaio quantitativo em tempo real para o DNA do vírus da hepatite B (HBV) desenvolvido para detectar todos os genótipos do HBV - Roberta Sitnik; Ângela Paes; Cristovão Pitangueira Mangueira; João Renato Rebello Pinho (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
Hepatitis B virus (HBV) is a major cause of chronic liver disease worldwide. Besides genotype, quantitative analysis of HBV infection is extensively used for monitoring disease progression and treatment. Affordable viral load monitoring is desirable in resource-limited settings and it has been already shown to be useful in developing countries for other viruses such as Hepatitis C virus (HCV) and HIV. In this paper, we describe the validation of a real-time PCR assay for HBV DNA quantification with TaqMan chemistry and MGB probes. Primers and probes were designed using an alignment of sequences from all HBV genotypes in order to equally amplify all of them. The assay is internally controlled and was standardized with an international HBV panel. Its efficacy was evaluated comparing the results with two other methods: Versant HBV DNA Assay 3.0 (bDNA, Siemens, NY, USA) and another real-time PCR from a reference laboratory. Intra-assay and inter-assay reproducibilities were determined and the mean of CV values obtained were 0.12 and 0.09, respectively. The assay was validated with a broad dynamic range and is efficient for amplifying all HBV genotypes, providing a good option to quantify HBV DNA as a routine procedure, with a cheap and reliable protocol. O vírus da Hepatite B (HBV) é uma das principais causas de doença crônica do fígado no mundo. Além do genótipo, a análise quantitativa do HBV é amplamente utilizada para monitorar a progressão da doença e o tratamento. Em locais com recursos escassos, métodos baratos para o monitoramento da carga viral são desejáveis e, em países em desenvolvimento, sua utilidade já foi demonstrada para outros vírus, como o da Hepatite C e HIV. Neste trabalho, descrevemos a validação de um teste de PCR em Tempo Real para a quantificação do DNA do HBV utilizando sondas Taqman/MGB. Os oligos e sondas foram escolhidos usando um alinhamento contendo seqüências de todos os genótipos do HBV para garantir uma amplificação igual de todos eles. O teste possui um controle interno e foi ...